2020
DOI: 10.1101/2020.08.26.268854
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Furin Cleavage Site Is Key to SARS-CoV-2 Pathogenesis

Abstract: SARS-CoV-2 has resulted in a global pandemic and shutdown economies around the world. Sequence analysis indicates that the novel coronavirus (CoV) has an insertion of a furin cleavage site (PRRAR) in its spike protein. Absent in other group 2B CoVs, the insertion may be a key factor in the replication and virulence of SARS-CoV-2. To explore this question, we generated a SARS-CoV-2 mutant lacking the furin cleavage site (ΔPRRA) in the spike protein. This mutant virus replicated with faster kinetics and improved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
208
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 199 publications
(222 citation statements)
references
References 39 publications
(41 reference statements)
6
208
0
2
Order By: Relevance
“…The mutant virus also had reduced replication in Calu3 human respiratory cells and had attenuated disease in a hamster pathogenesis model. These results showed an important role of the furin cleavage site in SARS-CoV-2 replication and pathogenesis (Johnson et al, 2020).…”
Section: Furin Cleavage Site Of the Spike Proteinmentioning
confidence: 73%
“…The mutant virus also had reduced replication in Calu3 human respiratory cells and had attenuated disease in a hamster pathogenesis model. These results showed an important role of the furin cleavage site in SARS-CoV-2 replication and pathogenesis (Johnson et al, 2020).…”
Section: Furin Cleavage Site Of the Spike Proteinmentioning
confidence: 73%
“…Furthermore, the original 2003 SARS-CoV lacked a furin CS and was clearly transmitted between people, although this usually occurred during a symptomatic phase rather than asymptomatically or pre-symptomatically, thus allowing the virus outbreak to be controlled by public health measures (Liu, Gayle, Wilder-Smith, & Rocklov, 2020). Several recent studies have investigated the pathogenicity of naturally occurring or engineered deletion mutants in the hamster model, and shown that viruses lacking the furin CS are attenuated for replication and pathogenicity (Johnson et al, 2020; Lau et al, 2020; Wang et al, 2020; Wong et al, 2020). We, like others, did not find that SARS-CoV-2 induced significant clinical signs in ferrets, so were unable to assess the effect of the CS mutation on viral pathogenesis here.…”
Section: Discussionmentioning
confidence: 99%
“…Proteases in the extracellular milieu, such as trypsin, thermolysin, and furin, may enhance the preprocessing of the S protein and reduce the dependency of intracellular proteases [83]. Similarly, furin has been shown to cleave at the SARS-CoV-2 spike at the S1/S2 site [65,84]. These might all be hints of the adaptive evolution of coronaviruses.…”
Section: Protease-mediated Priming Of the Spike Proteinmentioning
confidence: 99%